The Effect of Digital Flashcard on Students’ Vocabulary Mastery: An Experimental Research at SMPN 12 Padang - Rika Permata Yulsardi; Ratmanida Ratmanida (Universitas Negeri Padang, 2021)
This research is a quasi-experimental research. The purpose of this research is to find out the effect of digital flashcard on students’ vocabulary mastery at SMPN 12 Padang. The population of this research were the first-year students of SMPN 12 Padang. The research sample was 27 students of class VII.3 as the experimental class and 27 students of class VII.9 as the control class. The instrument of this research was vocabulary test that was conducted into two tests, pre-test and post-test. The instrumentation was created into 20 short answer questions. Based on the data analysis by using Paired Sample T-test in SPSS 26 for windows, the mean of pre-test score in experimental class was 47.2 while the mean of post-test score in experimental class was 82.0. It can be concluded that the students’ who are taught by using digital flashcard as teaching media are better than students’ who are taught by using conventional media. The significance of the test is 0.000 which is lower than the significance level that is 0.05 with 5% of degree. Moreover, it is also found that the students’ score is improving especially for the students in experimental class which gained 34.8 of their average score.